K-12, university students and robots: an early start - Soares, Filomena (2011)
This paper describes a study carried out with K-12 students. This study proposes to understand the motivation of these students in the use of robots in the Project Area curricular unit and whether they want to continue their studies in technology areas. K-12 students participated in the RoboParty® event, where the main task is to assemble and program a robot. In other words, the students, in a simple and entertaining way and supported by qualified tutors, learned how to build a robot. At the end of the academic year, a questionnaire was applied to identify and evaluate the K-12 students' opinions regarding the experience. The students’ reaction to this experience was quite positive as well the direct contact with the university environment.